If it's not what You are looking for type in the equation solver your own equation and let us solve it.
u in (-oo:+oo)
(5/3)*u-1 = (-1/2)*u-(1/2) // - (-1/2)*u-(1/2)
(5/3)*u-((-1/2)*u)+1/2-1 = 0
(5/3)*u+(1/2)*u+1/2-1 = 0
13/6*u-1/2 = 0 // + 1/2
13/6*u = 1/2 // : 13/6
u = 1/2/13/6
u = 3/13
u = 3/13
| 2=y+x+7 | | y/2-5=y/3-4 | | 30/6=10/n | | 7n+14=-21 | | 3x*x+4=16 | | y=3y^2-5 | | 77=8x | | 17x+1=19x-7 | | 3(4w)= | | 0-2=12-2*5-5 | | 4(2x-1)+3(x-5)=14 | | 7.6x-3.7=-62.4 | | 4w*3= | | 3x+3=9x+18 | | 4/10=2/x | | 2x+x=3800 | | 5n/28-6/7=13/4 | | x/3-12=27 | | 2(x-3)/3 | | X(5x-4)=(5x+1)(x-3) | | 4x+6-x-9=3(x+5) | | 2x+13x=17+3 | | (z*10)-7=1 | | Senx=-0.22 | | 2x+3x=17+3 | | -4(3x-5)=-5x-20-3x | | n+4+39=95 | | y=5c | | F(x)=-X^4-x^3+1 | | 3v+8=23 | | M-6m+3m+1= | | 32=2a |